Experience in the use of antiviral drugs in the treatment of conjunctivitis in COVID–19 - Meyramov, G.G.; Muntinov, Zh.D.; Korchin, V.I.; Abikenova, F.S.; Abdrakhmetova А.К.; Ospanov М.Т.; Omarov, D.N. (Fundamental and Experimental Biology, 2022)
The study presents the effect of the drug Favipiravir in the complex therapy of conjunctivitis caused by COVID–19. The diagnosis of coronavirus infection was confirmed by positive PCR tests; the severity was assessed based on fluoroscopic examination of the lungs and computed tomography. To treat eye symptoms of conjunctivitis caused by SARS-CoV-2, antiviral drugs have been used: Acyclovir, Ophtalmoferon, and Favi-piravir. The authors have shown that treatment with Favipiravir in combination with antiviral drugs reduces the duration of treatment by 1.86 times in patients of group 2 compared to patients of the first group who were treated with acyclovir and Оphthalmoferon. The high effectiveness of treatment of conjunctivitis withFavipi-ravir is due to the mechanism of its tropic action in relation to RNA-containing viruses, due to its ability to integrate into the RNA chain of the COVID-19, inhibiting its RNA-dependent RNA polymerase and disrupt the replication of the coronavirus. In addition, Favipiravir induces lethal RNA transversion mutations, leading to the death of the virus. The prolongation of the duration of treatment of conjunctivitis in patients of the first group can be explained by the effect of Аcyclovir, aimed at inhibiting viral DNA polymerase and blocking the synthesis of viral DNA, while the COVID-19 belongs to a single-stranded RNA-containing virus, despite the action of Оphthalmoferon, which can disrupt the reproduction of the virus by interacting with specific membrane receptors, the CD147 protein of the conjunctival epithelium.